Inguinal Hernia in Athletes: Role of Dynamic Ultrasound - Vasileff, William Kelton (Sports Health, 2017)
BACKGROUND: Inguinal hernia is a commonly encountered cause of pain in athletes. Because of the anatomic complexity, lack of standard imaging, and the dynamic condition, there is no unified opinion explaining its underlying pathology. HYPOTHESIS: Athletes with persistent groin pain would have a high prevalence of inguinal hernia with dynamic ultrasound, and herniorrhaphy would successfully return athletes to activity. STUDY DESIGN: Case-control study. LEVEL OF EVIDENCE: Level 3. METHODS: Forty-seven amateur and professional athletes with sports-related groin pain who underwent ultrasound were selected based on history and examination. Patients with prior groin surgery or hip pathology were excluded. Clinical and surgical documentation were correlated with imaging. The study group was compared with 41 age-matched asymptomatic athletes. RESULTS: Ultrasound was positive for hernia with movement of bowel, bladder, or omental tissue anterior to the inferior epigastric vessels during Valsalva maneuver. The 47-patient symptomatic study group included 41 patients with direct inguinal hernias, 1 with indirect inguinal hernia, and 5 with negative ultrasound. Of 42 patients with hernia, 39 significantly improved with herniorrhaphy, 2 failed to improve after surgery and were diagnosed with adductor longus tears, and 1 improved with physical therapy. Five patients with negative ultrasound underwent magnetic resonance imaging and were diagnosed with hip labral tear or osteitis pubis. The 41-patient asymptomatic control group included 3 patients with direct inguinal hernias, 2 with indirect inguinal hernias, and 3 with femoral hernias. CONCLUSION: Inguinal hernias are a major component of groin pain in athletes. Prevalence of direct inguinal hernia in symptomatic athletes was greater than that for controls (P < 0.001). Surgery was successful in returning these athletes to sport: 39 of 42 (93%) athletes with groin pain and inguinal hernia became asymptomatic. CLINICAL RELEVANCE: Persistent groin pain in the athlete may relate to inguinal hernia, which can be diagnosed with dynamic ultrasound imaging. Herniorrhaphy is successful at returning athletes to sports activity.